Why Isn't 2 2 Factored Out?

Calculus Level 3

0 π e x ( 6 cos 3 x 8 sin 3 x ) d x \int_0^\pi e^x(6\cos 3x - 8\sin 3x) dx Evaluate the given integral to two decimal places.


The answer is -72.42.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Naren Bhandari
May 26, 2018

We have I = 0 π e x ( 6 cos 3 x 8 sin 3 x ) d x = 0 π ( 6 e x cos 3 x 8 e x sin 3 x ) d x I = 0 π 6 e x cos 3 x 0 π 8 e x sin 3 x d x = 6 I 1 8 I 2 I = \int_{0}^{\pi} e^x(6\cos 3x - 8\sin 3x) \,dx = \int_{0}^{\pi} \left(6e^x\cdot \cos 3x - 8e^x \sin 3x\right)\,dx \\ I = \int_{0}^{\pi} 6e^x\cdot \cos 3x - \int_{0}^{\pi} 8e^x \sin 3x \,dx = 6I_1 -8 I_2 We can directly use the general formula for evaluating the integrals I 1 I_1 and I 2 I_2 . However, lets evaluate without using the general formula. I 1 = e x cos 3 x = e x cos 3 x ( 3 sin 3 x e x ) d x I 1 = e x cos 3 x + 3 ( e x sin 3 x 3 ( e x cos 3 x ) d x ) = e x sin 3 x + 3 e x cos 3 x + 9 I 1 I_1 = \int e^x\cos 3x= e^x\cos 3x - \int\left(-3\sin 3x \cdot e^x\right)\,dx\\ I_1 = e^x\cos 3x +3\left(e^x\sin 3x -3\int(e^x\cdot \cos 3x)\,dx\right) = e^x\cdot \sin 3x +3e^x\cdot \cos 3x + 9I_1 I 1 = 3 e x sin 3 x + e x cos 3 x 10 \implies I_1 =\dfrac{ 3 e^x\cdot \sin 3x +e^x\cdot \cos 3x}{10} .On the same manner using Integration by parts we can evaluate integral I 2 I_2 as I 2 = e x sin 3 x 3 e x cos 3 x 10 I_2 = \dfrac{e^x\cdot \sin3x -3e^x\cdot \cos 3x}{10} Hence I = 6 10 ( 3 e x sin 3 x + e x cos 3 x ) 8 10 ( e x sin 3 x 3 e x cos 3 x ) I = e x ( sin 3 x + 3 cos 3 x ) 0 π = 3 e π 3 72.4220 I = \dfrac{6}{10}\left(3 e^x\cdot \sin 3x +e^x\cdot \cos 3x\right) - \dfrac{8}{10}\left(e^x\cdot \sin3x -3e^x\cdot \cos 3x\right) \\ I = e^x\left(\sin 3x + 3\cos 3x\right)\large |_{0}^{\pi} = -3e^{\pi}-3 \approx \boxed{-72.4220}

Nice solution. But my intention was for everyone to recognize that the question is in the following form e x ( f ( x ) + 2 f ( x ) + f ( x ) ) d x = e x ( f ( x ) + f ( x ) ) + C \int e^x(f(x)+2f'(x)+f''(x))dx=e^x(f(x)+f'(x))+\mathbb C

Sravanth C. - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...